A feasibility study on the ZiGreen Power Manager - Calma, Pauline Carol; Palconit, Amy; Tanyag, Sharmaine Ann
ZiGreen Power Manager, an undergraduate research under the Electrical and Engineering Institute (EEEI) of the University of the Philippines Diliman, is a wireless device which could effectively control air-conditioning units. It has other features such as monitoring of real-time consumption of electricity and direct load control. Furthermore, it has 3 main components: the smart box, household control box and master controller. With its energy-saving feature, this study aims to assess the feasibility of this project over the first 5 years. The study is divided into three main parts: market, technical and financial study. For the first part, the product description was finalized and was used to determine the response of the possible market. Market segmentation was done to determine the best initial target market for the product. The market was determined to be 3-star hotels (37 hotels) within Metro Manila. The number of hotel establishments is expected to increase by 3% every year. This was also used to determine the target number of hotels per year. Moreover, only indirect competitors were identified since the product is classified as "first in the Philippines". A push system of marketing strategy will be used by the company to attract potential customers. The number of target hotels varies every year: 5, 7, 8, 10 and 13 hotels for years 1 to 5, respectively. Also different packages will be offered to the hotels depending on their desired number of rooms. With these marketing strategies, marketing costs and sales projections were made. For the technical study part, production processes and plant capacity were identified using the projected demand of the product A commercial space in Quezon Avenue, Quezon City was chosen to be the location of the office and manufacturing facility. For the supplier of raw materials, Alexan Commercial was chosen among the different alternatives that were considered. Furthermore, the manufacturing process was assessed to be manpower intensive since manual production will be used. Approximately, 3 hours and 35 minutes is needed to manufacture one package of this device. The number of assemblers and quality control managers will vary every year to satisfy the projected demand for the different packages. With the data gathered, an initial investment cost of Php3 million pesos is needed to fund the start-up costs of the business and the required operating costs for year 1. This will be funded through soft loans from friends and families of the owners of the company. A potential profit of Php 41.8 million pesos was then calculated at the end of the technical study. The organizational structure that wil1 be used by the company is a general partnership type. Work hours, compensations, benefits and trainings were considered for employees. The last part involves the financial study. An increasing net income was generated in the Pro-Forma Income Statement. Liquidity, profitability, and debt-to-equity ratios were computed to determine the performance of the business. Acceptable values for the liquidity, profitability and debt-to-equity ratios were generated. Also, the net present value of the business is Php 36.1 million and the internal rate of return which is 88% was higher than estimated. Thus, the project was assessed to be feasible after the market, technical and financial studies were conducted.